Choosing Appropriate Retrieval based Learning Elements among Students in Java Programming Course - Azizah Bt Aziz, Noor; Bin Udin, Amirmudin; Subari, Kamarularifin; Ismail, Sarimah (International Journal of Psychosocial Rehabilitation, 2020)
Effective learning needs consistent and relevant strategies to help students process and maintain new information. This importance is influenced by researchers’ objectives to help students who are able to retain memory in learning and manage to master learning well. Encoding, learning condition, and learning practice are the important elements in retrieval-based learning (RBL) strategies. This research aims to decide suitable RBL strategies for students who join the Java Programming course at vocational institutions. The research sample consists of 72 DVM students in their first semester for the Data and Web Application Database Management course in four different vocational institutions. Research data were obtained using a questionnaire and analyzed using the Statistical Package of the Social Sciences (SPSS) software version 22.0. The questionnaire was divided into four sections: encoding, learning condition, retrieval practice, and suitable materials to be used in learning. Results from the descriptive analysis showed that the use of encoding through acoustic, visual semantic, and elaborative methods has become students’ choice in program learning, while the appropriate learning condition for students with the highest mean value of 4.0694 is through repetitive practices or individual tests to improve memory in learning. The three retrieval practices, which are free recall, serial recall, and cue recall, receive the highest interpretation other than using hardcopy materials and computer applications in learning. Students’ learning approaches were different depending on suitability and comfort. Thus, educators should realize this and the effort of adapting learning between students’ choices and the Java Programming course, which could create an effective learning environment for all students. The results of the study are hoped to provide important knowledge in improving program learning, generally, and at vocational institutions, specifically, for computer programming courses.